HUBUNGAN PENGGUNAAN GADGET DENGAN KETAJAMAN PENGLIHATAN PADA SISWA KELAS IV DI SD NEGERI 7 AMBON - Harianti Fajar; Davita S. Batoek (Pasapua Health Journal, 2020)
Introduction: Visual acuity is the ability to distinguish small details, both on objects and on surfaces. However, the behavior of using gadgets increases the risk of decreasing this vision. Gadgets are not only used by teenagers and adults, but also used by school age groups Method: The research method is a descriptive analytic observational study using the Cross Sectional4 approach. The research was conducted in October 2019 at SD Negeri 7 Ambon. Visual acuity was measured on the Snellen chart. The population of all fourth grade students at SD Negeri 7 Ambon totaling 45 people. Result : The results of the Chi Square statistical test showed a significant value of 0.000 which means that there is a relationship between gadget use and visual acuity in students at SD Negeri 7 Ambon. Conclusion: the use of gadgets has a risk of affecting the sharpness of the eyes in children at SD Negeri 7 Ambon